2001
DOI: 10.1154/1.1402627
|View full text |Cite
|
Sign up to set email alerts
|

Comments on determining X-ray diffraction-based volume fractions of retained austenite in steels

Abstract: Retained austenite is an important characteristic of properly heat-treated steel components, particularly gears and shafts, that will be subjected to long-term use and wear. Normally, either X-ray diffraction or optical microscopy techniques are used to determine the volume percent of retained austenite present in steel components subjected to specific heat-treatment regimes. As described in the literature, a number of phenomenological, experimental, and calculation factors can influence the volume fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The XRD analysis for RA is strongly affected by alloying elements and carbides. Given the high level of alloying elements in the material it should be noted that the accuracy will be less than typically achieved by XRD (vander Voort and Manilova, 2005;Lowe-Ma and Donlon, 2001).…”
Section: Investigation Of the 'Tiger Skin' Defect On Indefinite Chillmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD analysis for RA is strongly affected by alloying elements and carbides. Given the high level of alloying elements in the material it should be noted that the accuracy will be less than typically achieved by XRD (vander Voort and Manilova, 2005;Lowe-Ma and Donlon, 2001).…”
Section: Investigation Of the 'Tiger Skin' Defect On Indefinite Chillmentioning
confidence: 99%
“…XRD was then done to analyse the phases present within the samples. The relative phase amounts (mass %) were estimated using the Rietveld method (Lowe-Ma and Donlon, 2001). The carbide morphologies and quantity data (as determined by microscopy) were used to ensure accurate RA peak identification to avoid erroneous overestimation.…”
mentioning
confidence: 99%
“…Broad distorted martensite peaks [15], metallic carbides, a strong preferred orientation of the material and improper R-values could also be considered as sources of errors in determination of the volume fraction of retained austenite. In this research work, however, the material was studied in a tempered condition and, thus, broad distorted martensite peaks were of no concern.…”
Section: Ra Measurementsmentioning
confidence: 99%
“…Regarding the theoretical R-values used, LoweMa et al [15] showed that the effect of using theoretical Rvalues in comparison to calculated values is rather small, and that this influence is inadequate for variations in measured results. However, this is only valid for low alloyed materials.…”
Section: Ra Measurementsmentioning
confidence: 99%
See 1 more Smart Citation